Spontaneous recovery of cochlear fibrocytes after severe degeneration caused by acute energy failure - Mizutari, Kunio (Frontiers in Pharmacology, 2014)
Cochlear fibrocytes in the lateral wall region play a critical role in the regulation of inner ear ion and fluid homeostasis, although these are non-sensory cells. Along with other non-sensory cells, fibrocytes in the spiral ligament have been reported to repopulate themselves after damage. However, the studies of regeneration of cochlear fibrocytes have been difficult because a suitable fibrocyte-specific degeneration model did not exist. Therefore, we analyzed cochlear fibrocytes using a rat model of acute cochlear energy failure induced by a mitochondrial toxin. This model is unique because hearing loss is caused by apoptosis of fibrocytes in the cochlear lateral wall not by damage to sensory cells. Although this model involves severe damage to the cochlear lateral wall, delayed spontaneous regeneration occurs without any treatment. Moreover, partial hearing recovery is accompanied by morphological remodeling of the cochlear lateral wall. Two hypotheses are conceivable regarding this spontaneous recovery of cochlear fibrocytes. One is that residual cochlear fibrocytes proliferate spontaneously, followed by remodeling of the functional region of the lateral wall. Another is that some foreign cells such as bone marrow-derived cells promote morphological and functional recovery of the lateral wall. Acceleration of the lateral wall recovery promoted by these mechanisms may be a new therapeutic strategy against hearing loss.